Factors Influencing Undergraduate Nursing Students’ Perception of Educational Quality - Sahar A. A. Ahmed; Sanaa M. Ahmed; Lamia A. Awad (Evidence-Based Nursing Research)
Context: Quality education is a contemporary concern. Students' evaluations of teaching (SET) are universal measures and applied in almost every higher educational system in the world.